2018
DOI: 10.1101/307165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genome ofEctocarpus subulatus– a highly stress-tolerant brown alga

Abstract: 35Brown algae are multicellular photosynthetic stramenopiles that colonize marine rocky shores 36 worldwide. Ectocarpus sp. Ec32 has been established as a genomic model for brown algae. Here we 37 present the genome and metabolic network of the closely related species, Ectocarpus subulatus 38Kützing, which is characterized by high abiotic stress tolerance. Since their separation, both strains 39show new traces of viral sequences and the activity of large retrotransposons, which may also be 40 related to the ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 99 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…The species E. subulatus (Peters et al 2015) is related to the genomic model species Ectocarpus siliculosus (Cock et al 2010) and has been reported in highly variable environments with high levels of abiotic stressors, such temperature at Port Aransas, Texas, USA (Bolton 1983). More recently, the genome of E. subulatus has been sequenced, revealing that E. subulatu s, in comparison to Ectocarpus siliculosus , has lost members of gene families down-regulated in low salinities, and conserved those that were up-regulated (Dittami et al 2018, preprint). The E. subulatus strain from Hopkins River Falls has further been used for physiological experiments: it can grow in both seawater and fresh water and its transcriptomic and metabolic acclimation to these conditions has been examined (Dittami et al 2012) along with the composition of its cell wall with regard to sulfated polysaccharides (Torode et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The species E. subulatus (Peters et al 2015) is related to the genomic model species Ectocarpus siliculosus (Cock et al 2010) and has been reported in highly variable environments with high levels of abiotic stressors, such temperature at Port Aransas, Texas, USA (Bolton 1983). More recently, the genome of E. subulatus has been sequenced, revealing that E. subulatu s, in comparison to Ectocarpus siliculosus , has lost members of gene families down-regulated in low salinities, and conserved those that were up-regulated (Dittami et al 2018, preprint). The E. subulatus strain from Hopkins River Falls has further been used for physiological experiments: it can grow in both seawater and fresh water and its transcriptomic and metabolic acclimation to these conditions has been examined (Dittami et al 2012) along with the composition of its cell wall with regard to sulfated polysaccharides (Torode et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The WSC domain family is one of the largest protein domain families in brown algae, with 444 members in Ectocarpus sp. strain Ec32 (Dittami et al 2020). Three of the 28 mannuronan C5-epimerase enzymes in Ectocarpus are predicted to possess WSC domains and, while their biochemical function has not been yet elucidated, these motifs may act as cell wall-binding domains, possibly targeting alginate (Michel et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Raw sequencing reads were quality-trimmed with Trimmomatic (version 0.36, minimal Phred score: 20, minimal read length: 36 nucleotides) and aligned to the E. subulatus Bft15b reference genome (Dittami, Corre, et al, 2020) using STAR aligner version 2.6.0a (Dobin et al, 2013) to remove algal reads. Non-aligning (i.e.…”
Section: Metagenome Analysesmentioning
confidence: 99%
“…Mutants of Arabidopsis and Cyanobacteria missing the last reaction of its biosynthetic pathway are viable but exhibit increased photosensitivity (Fatihi et al, 2015). In E. subulatus, just as in E. siliculosus, Saccharina latissima, and Cladosiphon okamuranus (Nègre et al, 2019;Dittami, Corre, et al, 2020), the last step of the vitamin K biosynthetic pathway is absent from the algal metabolic network. It suggests that these algae cannot produce vitamin K independently, although this compound has previously been detected in kelps (Yu et al, 2018).…”
Section: Loss Of Microbial Services In Non-tolerant Holobionts: Vitamin Kmentioning
confidence: 99%